2021
DOI: 10.1088/1367-2630/ac17b9
|View full text |Cite
|
Sign up to set email alerts
|

Extremely flat band in antiferroelectric bilayer α-In2Se3 with large twist-angle

Abstract: The moiré-pattern with slightly interlayer-twisted bilayer two-dimensional (2D) materials has recently been receiving substantial attention. One of the major characters for these intriguing structures is the appearance of low-energy ultra-flat bands and thus a package of new physics associated with strong electron correlation emerges. However, such new physics may become vague unless the twist-angle θ is sufficiently small such as θ ∼ 1°, making practical applications and control-flexibility hard to handle. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…θ = 13.17°, due to the appearance of moiré-patter. 157 Afterwards, a similar situation was also observed in the twisted bilayer InSe, 158 in which the bandwidth can be suppressed to be less than 10 meV at θ = 9.43°. Recently, Chen et al proved that the two Fe 3 GeTe 2 layers can implement an antiferromagnetic–ferromagnetic phase transition by constructing an interlayer rotation, 159 providing a feasible method to tune the interlayer magnetic ordering of 2D compounds.…”
Section: Controllable Fabricationsupporting
confidence: 64%
“…θ = 13.17°, due to the appearance of moiré-patter. 157 Afterwards, a similar situation was also observed in the twisted bilayer InSe, 158 in which the bandwidth can be suppressed to be less than 10 meV at θ = 9.43°. Recently, Chen et al proved that the two Fe 3 GeTe 2 layers can implement an antiferromagnetic–ferromagnetic phase transition by constructing an interlayer rotation, 159 providing a feasible method to tune the interlayer magnetic ordering of 2D compounds.…”
Section: Controllable Fabricationsupporting
confidence: 64%
“…For example, a graphene bilayer, even regularly stacked as a periodic lattice, has possessed electronic structures and transport properties significantly different from those of a monolayer one [14]. By twisting bilayers into generic non-commensurate or quasi-periodic lattices, more nontrivial physics emerge, including strong correlation, superconductivity and nontrivial topology [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that MPDs are antiferroelectric [56,57]. Although in 3R-stacked homo-bilayers the domains have opposite orientation and the polarization averages to zero, the classical definition of antiferroelectricity refers to anti-aligned adjacent dipoles, not adjacent domains, analogous to an antiferromagnet.…”
Section: B Comparison With Conventional Ferroelectricsmentioning
confidence: 99%